Trends in, and predictors of, swallowing and social eating outcomes in head and neck cancer survivors: A longitudinal analysis of head and neck 5000. (July 2021) - Patterson, Joanne M.; Lu, Liya; Watson, Laura-Jayne; Harding, Sam; Ness, Andy R.; Thomas, Steve; Waylen, Andrea; Waterboer, Tim; Sharp, Linda
Highlights: Swallowing and eating deteriorates post-treatment, with some recovery by one year. Multi-modal treatment and age predict swallowing and social eating at one year. Low SES, sex, smoking, living alone contribute towards poorer swallowing and eating. Oropharyngeal cancer survivors have poorer outcomes in comparison to other sites. Abstract: Objective: To investigate the recovery trajectory and predictors of outcome for swallowing difficulties following head and neck cancer treatment in a large prospective cohort. Materials and methods: Data from 5404 participants of the Head and Neck 5000 study were collected from 2011 to 2014. Patient-reported swallowing was measured using the EORTC HN35, recorded at baseline (pre-treatment) and 4 and 12 months post-baseline. Mixed-effects linear multivariable regression was used to investigate time trends, compare cancer sites, and identify associations between clinical, socio-demographic and lifestyle variables. Results: 2458 participants with non-recurrent oral (29%) oropharyngeal (46%) and laryngeal (25%) cancer were included in the analysis. There was a clinically significant deterioration in scores between baseline and four months for swallowing (11.7 points; 95% CI 10.7–12.8) and trouble with social eating (17.9 points; 95% CI 16.7–19.2), but minimal difference between baseline and 12 months. Predictors of better swallowing and social eating were participants with larynx cancer, early-stage disease, treatment type, age, gender, co-morbidity, socio-economic status, smoking behaviour and cohabitation. Conclusion: Swallowing problems persist up to a year after head and neck cancer treatment. These findings identify disease and demographic characteristics for particularly vulnerable groups, supporting the need for holistic interventions to help improve swallowing outcomes. People diagnosed with head and neck cancer at risk of severe eating and drinking problems following treatment can be identified earlier in the pathway, receive more accurate information about early and late post-treatment side-effects, which can inform shared decision-making discussions.